Deteksi Perkembangan Balita di PAUD Cahaya - Iis Pusparina; Filia Sofiani Ikasari; Dewi Irianti (Jurnal Pengabdian Bidang Kesehatan, 2023)
Growth and development are two different processes that cannot be separated and are equally important for children in the critical period of the first 0-5 years of life because they will have implications for the child's quality of life in the future. This phase is often referred to as the "Golden Age" phase. Golden age is a very important period to pay close attention to a child's growth and development so that abnormalities can be detected as early as possible. This monitoring must be carried out regularly and continuously. Early age is a golden period and an important stage in the child's growth and development process considering that at this stage rapid development occurs and has long-term effects. Therefore, early detection needs to be done so that parents or teachers can anticipate it early so that growth and development disorders do not occur continuously. In Sungai Tuan Ulu village there is a growth measurement service at Posyandu which is carried out every month but so far there has never been a measurement of development, especially for toddlers at Cahaya PAUD. The use of the Pre-Developmental Screening Questionnaire (KPSP) as a developmental screening tool up to the age of 6 years really helps with careful development. Parents and teachers need to know the current development of their toddlers. So that if a developmental delay is found, it can be handled immediately. Therefore, the activities carried out in community service include early detection of toddler development with KPSP.